Methods Open - A New Journal Track Starting in 2017 - Koch, Sabine; Haux, Reinhold; Gefeller, Olaf; Sarkar, Indra N.; Bergemann, Dieter (Methods of Information in Medicine, 2016)
From 2017 (volume 56) onwards the journal Methods of Information in Medicine will consist of two tracks. Authors can decide to submit their manuscript to either the subscription track that continues to publish its six print and electronic (non-open access) issues for journal subscribers, or the new Methods Open track that will consist of digitally published manuscripts (as gold open access). These two tracks will constitute from 2017 on the journal's Tandem Model. Simultaneously, Methods will introduce a double-blinded review process and reviewer assessment by the submitting authors. Implications of these changes for both authors and reviewers are discussed. With these steps, Methods aims to improve the visibility of the journal and contribute to sharing research results as timely and as widely as possible and thereby to promote scientific progress.
EVALuna2:5571